1994
DOI: 10.1073/pnas.91.16.7520
|View full text |Cite
|
Sign up to set email alerts
|

D-mef2: a Drosophila mesoderm-specific MADS box-containing gene with a biphasic expression profile during embryogenesis.

Abstract: We have identified a mesoderm-specific Drosophila gene, desigatedD-mef2. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(108 citation statements)
references
References 31 publications
(31 reference statements)
4
102
2
Order By: Relevance
“…The role of MEF2 in muscle formation has been demonstrated most clearly in D. melanogaster, which contains a single Mef2 gene, D-mef2 (21,37). Inactivation of D-mef2 results in embryos lacking differentiated skeletal, cardiac, and visceral muscle (1,22,42).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of MEF2 in muscle formation has been demonstrated most clearly in D. melanogaster, which contains a single Mef2 gene, D-mef2 (21,37). Inactivation of D-mef2 results in embryos lacking differentiated skeletal, cardiac, and visceral muscle (1,22,42).…”
Section: Discussionmentioning
confidence: 99%
“…2A, the coding region of Mef2b contained seven exons and spanned about 3.5 kb. The positions of the introns in the region encoding the MADS box and MEF2 domain correspond exactly to those in the other vertebrate Mef2 genes (28) and in the Drosophila Mef2 gene, Dmef2 (21,37).…”
Section: Mef2b Is the Most Divergent Of The Vertebrate Mef2 Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…3H). Double labeling experiments with anti-DSema 5C, anti-bGal in the rp298 enhancer trap line (Nose et al, 1998), and anti-DMEF2 (Nguyen et al, 1994) muscle marker showed that DSema 5C is not present in muscle progenitors or the mature muscles (Fig. 4D-I).…”
Section: Dsema 5c Rna and Protein Are Expressed In Mesodermal Precursmentioning
confidence: 99%
“…Dmef2 is the sole Drosophila member of the Myocyte Enhancing Factor 2 (MEF2) family of transcription factors (Nguyen et al, 1994). Dmef2 is required for the differentiation of mesodermal tissues within the developing Drosophila embryo, specifically the body wall, visceral and cardiac muscles (Bour et al, 1995;Lilly et al, 1995;Lin et al, 1996;Ranganayakulu et al, 1995).…”
Section: Resultsmentioning
confidence: 99%